Perbedaan Modal, Profitabilitas dan Kredit Bermasalah Saat Perubahan Indikator Ekonomi - I Nyoman Nugraha Ardana Putra; Busaini Busaini; Sujadi Sujadi (Universitas Mataram, 2023)
The COVID-19 pandemic has had a real impact on changes in the form of an increase or decrease in economic indicators. The market shows that economic conditions in general are experiencing a decline so this of course has a major impact on business activities. This study aims to analyze the differences in capital, profitability and non-performing loans. This type of comparative research compares profitability and efficiency at Rural Banks (BPR) in West Nusa Tenggara before the decline in inflation and interest was lowest during the pandemic and after the lowest decline occurred. The analytical tool used is the t test (different test) 2 paired samples. The results of this study indicate that there is no difference before and after the decline in inflation and interest rates related to capital, profitability and non-performing loans.